Digitalising Traditional Markets: Challenges and Opportunities for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia - Hempri Suyatna; Kafa Abdallah Kafaa; Mohammad Farid Budiono; Rindu Sanubari Mashita Firdaus; Istianto Ari Wibowo (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2026)
Using a qualitative case study approach conducted from May 2020 to August 2021, this study investigates how traditional markets, namely the Sambilegi and Kolombo markets, work with digitalisation in Indonesia. It focuses on collective-based digital initiatives in terms of their implementation and sustainability amid increasing competition with modern e-commerce platforms. Within the broader context of Indonesia's economic development, the informal economy that is strongly dominated by micro, small, and medium enterprises (MSMEs) remains crucial for national growth. Findings from observations and field interviews with market stakeholders show that the influence of social capital is twofold; while it can strengthen transformation through shared commitment and collaboration, it can also hinder progress and innovation among stakeholders in traditional markets. Furthermore, the sustainability of collective-based digitalisation faces challenges when met with limited digital literacy, insufficient motivation, and inconsistent mentorship programmes. The study concludes that capacity-building and persistent institutional support, as well as a robust governance framework, have the potential to ensure long-term success in digitalising traditional markets. The study extends an understanding of how social capital ushers in digital transformation, along with strategies to sustain it within the Indonesian traditional market context.